2017
DOI: 10.19056/ijmdsjssmes/2017/v6i1/125560
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Injuries Due to Road Traffic Accidents in Saudi Arabia: A Review of Incidence, Demographic Factors & Prevention Strategies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…4,5,6 The WHO has documented that nearly one-third of traumatic injuries reported in developing countries are due to road traffic accidents (RTA) which significantly contribute towards increased mortality rates. 7,8 The purpose of the current study was to assess the association of age, gender, and mechanism of injuries in patients presenting at tertiary care facilities of Karachi, Pakistan. Locally reported data have shown that males are more prone to facial injuries during their 2nd and 3rd decades of life with the most common etiologic factor being road traffic accidents (RTA).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 The WHO has documented that nearly one-third of traumatic injuries reported in developing countries are due to road traffic accidents (RTA) which significantly contribute towards increased mortality rates. 7,8 The purpose of the current study was to assess the association of age, gender, and mechanism of injuries in patients presenting at tertiary care facilities of Karachi, Pakistan. Locally reported data have shown that males are more prone to facial injuries during their 2nd and 3rd decades of life with the most common etiologic factor being road traffic accidents (RTA).…”
Section: Introductionmentioning
confidence: 99%